Complex interplay of body condition, life history, and prevailing environment shapes immune defenses of garter snakes in the wild - Palacios, Maria Gabriela (2013)
The immunocompetence "pace-of-life" hypothesis proposes that fast-living organisms should invest more in innate immune defenses and less in adaptive defenses compared to slow-living ones. We found some support for this hypothesis in two lifehistory ecotypes of the snake Thamnophis elegans; fast-living individuals show higher levels of innate immunity compared to slow-living ones. Here, we optimized a lymphocyte proliferation assay to assess the complementary prediction that slowliving snakes should in turn show stronger adaptive defenses. We also assessed the "environmental" hypothesis that predicts that slow-living snakes should show lower levels of immune defenses (both innate and adaptive) given the harsher environment they live in. Proliferation of B- and T-lymphocytes of free-living individuals was on average higher in fast-living than slow-living snakes, opposing the pace-of-life hypothesis and supporting the environmental hypothesis. Bactericidal capacity of plasma, an index of innate immunity, did not differ between fast-living and slow-living snakes in this study, contrasting the previously documented pattern and highlighting the importance of annual environmental conditions as determinants of immune profiles of free-living animals. Our results do not negate a link between life history and immunity, as indicated by ecotype-specific relationships between lymphocyte proliferation and body condition, but suggest more subtle nuances than those currently proposed.